THE LEADERSHIP ROLE OF MADRASAH HEADS IN IMPROVING TEACHERS' PEDAGOGICAL COMPETENCE IN MEDAN CITY - Satriyadi, Satriyadi; Asmayani, Asmayani; Santoso, Didik; Sari, Selpi Trianda (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to find out the leadership role of madrasah heads in improving the pedagogical competence of teachers in Medan City. Pedagogical competence is one of the basic competencies that teachers must have to create an effective and meaningful learning process. The research method used is qualitative descriptive, with data collection techniques through observation, in-depth interviews, and documentation. The subjects in this study are school principals, teachers in the city of Medan, while the objects in this study are several schools in the city of Medan. After the data was collected, the researcher carried out data analysis through several stages, namely data reduction, data presentation, conclusion drawing and verification. Furthermore, the researcher carried out a data validity test using triangulation and member check. The results of the study show that visionary, communicative, and participatory leadership of madrasah heads has a positive influence on improving teachers' pedagogical competence. The head of the madrasah plays an active role in providing coaching, facilitating training, and creating a work climate that supports the development of teacher professionalism. This study concludes that the leadership role of madrasah heads is very important in fostering and directing teachers to continue to develop in pedagogical aspects, which ultimately has an impact on improving the quality of education in madrasas